Social Vulnerability and Human Development of Brazilian Coastal Populations - Curi, Rodrigo Luis Comini; Gasalla, Maria A. (Frontiers in Ecology and Evolution, 2021)
There is a considerable gap on linking the human dimensions and marine ecosystem services with the sustainable development goals, and one of the issues relates to the different perspectives and ideas around human development concepts. There is also a lack of contemporary evaluations of coastal communities under the lens of well-being and social vulnerability indexes of developing nations. This study contributes to that discussion by presenting an analysis of coastal municipalities of Brazil, based on two indexes: Social Vulnerability Index (SVI) and Municipal Human Development Index (MHDI). These indicators intend to map some aspects of social well-being and development in the Brazilian territory under different perspectives. MHDI illustrates the average populational conditions in a certain territory for humans to thrive, while the SVI points more specifically the lack of assets necessary for well-being in a territory. Overall, 65.9% and 78% of a total of 387 Brazilian coastal municipalities were ranked below SVI and MHDI country average values, respectively. Both indexes indicated higher well-being conditions in Southern municipalities than in Northern ones, especially for income and education conditions. However, natural capital and the presence of traditional populations with strong cultural heritage are key aspects to also be considered suggesting that the type of socio-economic development needed in Brazilian coastal zones are far from the current economic growth model. The use of indicators showed great value to track regional discrepancies and to guide decision-making. They should be taken with caution for improving well-being performance if disconnected from natural and cultural capital.